Behavioral effects on the offspring of rodent mothers exposed to Tetrahydrocannabinol (THC): A meta-analysis - Ramírez, Simón; Miguez, Gonzalo; Quezada-Scholz, Vanetza E.; Pardo, Luis; Alfaro, Felipe; Varas, Felipe I.; Laborda, Mario A. (Frontiers in Psychology, 2022)
Pre and perinatal administration of Tetrahydrocannabinol (THC) in rodents and their offspring has many effects that have been studied using different methods that have not been integrated using quantitative methods. The effect of THC administration on behavior can be better understood by meta-analytic techniques. We examined whether there is an overall effect on the behavior of the offspring when THC is administered to mothers. Eligibility criteria included experiments using an experimental design with a control group without THC, in which THC is administered to mothers during pregnancy and lactation in rodents, and in which at least one type of behavioral (locomotor, emotional or cognitive) measurement in the offspring was implemented. Cohen's d was obtained for each study, then each individual study was weighted, and moderator analysis was performed. Analysis was performed using fixed and random effect models, and the heterogeneity was assessed by calculating Qb, I2 and the prediction interval. Furthermore, 3 sub-meta-analyses were carried out according to the type of behavior. The general analysis determined a low weighted effect size of THC on the behavior of the offspring, moderated by type of rat strain. The sub-meta-analyses showed a medium effect for cognitive effects of THC in the offspring, and a low effect on locomotor activity and emotional behavior. In addition, publication bias was not detected. More research is needed to contribute to the understanding of the effect of THC exposure on offspring.